Treatment of pediatric spine disorders - Lastikka, Markus (fi=Turun yliopisto|en=University of Turku|, 2020)
Idiopathic scoliosis treatment options include bracing and surgery. Because of the great growth potential of the spine in juvenile idiopathic scoliosis (JIS) the right length of the fusion remains unknown. In adolescent idiopathic scoliosis (AIS) it is not yet established which is the best rod alternative. Surgery of the cervical spine is rare and complicated. The goals of this thesis were to study: (1) which brace treatment is more effective in main thoracic AIS, a night-time or full-time brace (Study I)? (2) Does posterior spinal fusion extended to the stable vertebra provide similar outcome in JIS patients compared with AIS patients with fusion to the last central sacral line touched vertebra (Study II)? (3) Which is the optimal rod alternative in deformity correction in adolescents operated for idiopathic scoliosis (Study III)? (4) To review the indications and outcomes of instrumented cervical spinal fusion in children (Study IV). In this study, the Providence night-time brace was as effective in the conservative treatment of main thoracic AIS as the Boston full-time brace. Posterior spinal fusion extended to the stable vertebra provides similar outcomes in JIS patients compared with AIS with fusion to the touched vertebra. Both circular and sagittal reinforced 6.0mm Cobalt-Chromium rods provide adequate coronal correction for adolescents operated for idiopathic scoliosis. The use of sagittal reinforced rods provides better thoracic kyphosis restoration. Skeletal dysplasia associated cervical instability and cervical spine injuries represented the most common indications for instrumented cervical spinal fusion in children. Occipitocervical (OC) spinal fusion and spinal fusion before the age of ten years are associated with higher risk of surgical complications and increased mortality than non-OC fusions and cervical spinal fusions at an older age.